Verification Of the Analysis Method For Determining Cetirizine HCl Levels in Cetirizine Syrup Preparations By High-Performance Liquid Chromatography According To The Compendial Method Of The Indonesian Pharmacopoeia, VIth Edition, 2020 - Nanda Putri Kamilah; Hasriyani Hasriyani; M. Khudzaifi (International Journal of Health Engineering and Technology, 2026)
Cetirizine Hydrochloride is a second-generation antihistamine that is effective for allergy therapy and is widely used in syrup dosage forms. The quality of drug preparations requires a valid assay analysis method to ensure the active substance content meets the requirements. This study aims to verify the analysis method for determining the content of Cetirizine Hydrochloride in syrup preparations using High Performance Liquid Chromatography (HPLC) in accordance with the Indonesian Pharmacopoeia Edition VI 2020 standards. The study was conducted at the Quality Control Laboratory of PT. X using an HPLC system equipped with an L10 column and UV detector set at 233 nm. Method verification parameters include system suitability testing, specificity, accuracy, precision, as well as linearity and range in determining the content of Cetirizine Hydrochloride. The results demonstrated that all verification parameters met the acceptance criteria. The system suitability test gave good results with an area RSD value of 0.232% and a tailing factor of 1.389. The method was proven to be specific with a retention time of 24.842 minutes without interference from the matrix. The accuracy of the assay method was confirmed with an average recovery value of 101.06% in the concentration range of 80–120% of the nominal concentration, and excellent precision with an RSD value of 0.31%. Linearity and range tests showed an excellent linear relationship in the concentration range of 80–120% with a correlation coefficient (r) of 0.9996. Based on these results, the analysis method for determining the content of Cetirizine Hydrochloride in syrup preparations was declared valid and suitable for use in routine quality control analysis.